Analisis Numerik Aliran Fluida di Sekitar Silinder Sirkular dengan Menggunakan Diskrititasi Order yang Berbeda - Muhammad Hasan Albana (Politeknik Negeri Batam, 2014)
Fluid flow around a circular cylinder is one of classical problems in fluid mechanics. Subsea pipeline and the pillars of offshore platform is an example from circular cylinder application. Many of these engineering applications are often subject to flow conditions correspondings to very high Reynolds number. The journal presents a numerical simulation of fluid flow around a two dimensional (2D) circular cylinder with high Reynolds number (Re = 2 × 106), steady Reynolds Average Navier Stokes (RANS), standar k - ???? SST and k – ???? SST turbulence model as well as using different order discretization; first order upwind, second order upwind dan third order MUSCL. The results are compared with published experimental data and numerical results. The k – ???? SST turbulence model are shown to be considerably more accurate than the standar k – ???? results. The use of different discretization order on the results of this study showed that the differences are not so significant.